The interfacial adhesion of wood fiber–reinforced UHMWPE composite filled with acid‐treated clay. (9th November 2017) - He, Runqin; Chang, Qiuxiang; Huang, Xinjun; Li, Jian
Abstract : Wood fiber–reinforced ultrahigh molecular weight polyethylene (wood fiber/UHMWPE) composites have been filled with acid‐treated clay to enhance the adhesion. According to the modification, the interlaminar shear strength of composites has been greatly improved. X‐ray photoelectron spectroscopy and scanning electron microscopy are used to examine the microscopic properties of resultant composites. The enhanced interlaminar shear strength is attributed to the clay interlock, which improves the wetting between wood fibers and resins.